(untitled) (Communication & Society, 2021)
This article analyses the opinions of citizens on the core values of the so-called Media accountability: truthfulness, independence, transparency, public participation and respect for peoples’ rights. It also analyses citizens’ perceptions of various deontological instruments to measure the effectiveness of compliance with these ethical values. The qualitative methodology used to carry out this analysis is part of the R+D+I research project “Accountability and Journalistic Cultures project in Spain. Impact and proposal of good practices in the Spanish media” (MediaACES), which has been achieved through six focus groups in different Spanish cities. The results of the analysis reflect the critical spirit of citizens towards the media due to the following factors: the absence of objectivity, the mixture of economic interests with their editorial line and an ambiguous participation of the public, which requires a better definition of their role within the information process. The conclusions derived from this analysis allow us to reflect on several aspects: among others, the competition in a deregulated market leads to infotainment and affects the quality of information, as well as the rights of people affected by the news. At the same time, the excess of information channels leads to greater disinformation, under the appearance of a spontaneous pluralism that is superfluous. Ethics, therefore, seems to be a necessary requirement to differentiate professional journalism from other inappropriate information channels and to guarantee the right to information of citizens.